Author Correction: AMP kinase promotes glioblastoma bioenergetics and tumour growth. Issue 11 (November 2018) - Chhipa, Rishi; Fan, Qiang; Anderson, Jane; Muraleedharan, Ranjithmenon; Huang, Yan; Ciraolo, Georgianne; Chen, Xiaoting; Waclaw, Ronald; Chow, Lionel; Khuchua, Zaza; Kofron, Matthew; Weirauch, Matthew; et al.
In the version of this Article originally published, in ref. 34 the first author's name was spelled incorrectly. The correct reference is: Rodón, L. et al. Active CREB1 promotes a malignant TGFβ2 autocrine loop in glioblastoma.Cancer Discov . 10, 1230–1241 (2014). This has now been amended in all online versions of the Article.